2015
DOI: 10.18632/oncotarget.3806
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictive factors of osteoporosis in systemic sclerosis patients: a case-control study

Abstract: PurposeInvestigate the prevalence of osteoporosis in patients with systemic sclerosis (SSc) and describe alterations of bone tissue with High-Resolution peripheral Quantitative Computed Tomography (HR-pQCT).MethodsThirty-three patients and 33 controls matched on age, body mass index (BMI) and menopause were included. Bone mineral density (BMD) was measured at the lumbar spine (LS), femoral neck (FN) and total hip (TH) by dual energy X-ray absorptiometry. Volumetric BMD (vBMD) and bone microarchitecture were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
1
14
2
15
Order By: Relevance
“…Other autoantibodies linked to bone disease and fragility fractures in existing literature, are anti-nuclear autoantibodies (ANA) and thyroid autoantibodies. Anti centromere and anti topoisomerase 1 (anti SCL70) autoantibodies have been observed to correlate with decreased BMD at various sites ( Marot et al, 2015 , Ibn Yacoub et al, 2012 ). Furthermore, a recent prospective study identified anti double stranded deoxyribonucleic acid (anti dsDNA) as an independent predictor of higher 10 year probability of hip fracture in SLE patients ( Mak et al, 2013 ).…”
Section: Autoimmunity and Osteoporosismentioning
confidence: 99%
“…Other autoantibodies linked to bone disease and fragility fractures in existing literature, are anti-nuclear autoantibodies (ANA) and thyroid autoantibodies. Anti centromere and anti topoisomerase 1 (anti SCL70) autoantibodies have been observed to correlate with decreased BMD at various sites ( Marot et al, 2015 , Ibn Yacoub et al, 2012 ). Furthermore, a recent prospective study identified anti double stranded deoxyribonucleic acid (anti dsDNA) as an independent predictor of higher 10 year probability of hip fracture in SLE patients ( Mak et al, 2013 ).…”
Section: Autoimmunity and Osteoporosismentioning
confidence: 99%
“…The presence of ACA was associated with lower bone mineral density in the same study. Digital ulceration was associated with lower total hip and femoral neck bone density 123 . Another study pointed out that earlier onset of menopause in SSc patients is associated with lower bone mineral density 124 .…”
Section: Sclerodermamentioning
confidence: 90%
“…In particular, anti-deoxyribonucleic acid (DNA) topoisomerase I autoantibodies have been noted to significantly correlate with BMD amongst a sample of Moroccan women with systemic sclerosis [ 105 ]. Additionally, anti-centromere autoantibodies have been identified as independent risk factors for bone damage amongst systemic sclerosis patients, whilst high anti-double-stranded DNA (dsDNA) autoantibody levels were observed to independently predict 10-year risk of incurring a hip fracture amongst SLE patients [ 20 , 106 ]. ANAs represent one of the least researched immune markers in relation to pathologic bone loss.…”
Section: Discussionmentioning
confidence: 99%